GLADI Program: Inclusive Nutrition Education and Anemia Prevention for Deaf Adolescents at SLBN 1 East Lombok - Marzoan, Ahmad Suwandi (Jurnal Pengabdian West Science, 2025)
Inclusive nutrition education and anemia prevention for deaf adolescents remain a significant challenge within the development of equitable public health. This community engagement program aimed to enhance nutritional literacy and raise awareness of anemia prevention among deaf students at SLBN 1 East Lombok. The intervention was conducted using a visual and participatory approach through the GLADI program (Gerakan Luar Biasa dan Mandiri / Extraordinary and Independent Movement). Educational strategies included the use of interactive learning tools such as the "My Plate" puzzle game and Focus Group Discussions (FGDs) conducted in Indonesian Sign Language (BISINDO). The two-day program consisted of nutrition education sessions, mentoring, and reflection-based evaluations. Findings indicated an improvement in students’ knowledge regarding nutritious food and anemia, along with the emergence of more critical attitudes toward unhealthy eating habits. Key challenges included frequent double carbohydrate consumption, perceptions of healthy food as expensive, and the extremely low intake of iron supplementation tablets. The results underscore the importance of synergy between families, teachers, and communities in building inclusive and health-promoting learning environments.